Exploring mudbrick architecture and its re-use in Artaxata, Armenia, during the 1st millennium BC. A multidisciplinary study of earthen architecture in the Armenian Highlands. - Marta Lorenzon; Benjamín Cutillas-Victoria; Elisabeth Holmqvist; Myrsini Gkouma; Luc Vrydaghs; Achim Lichtenberger; Torben Schreiber; Mkrtich Zardaryan (PLoS ONE, 2023)
Mudbrick constructions are extremely common in ancient western Asia, including the 1st millennium structures of the southern Caucasus and Armenian highlands. However, in the Caucasus the geoarchaeological study of these materials to provide insight into building practices and social structure is a topic little researched, especially when focusing on the longue durée. Artashat/Artaxata (Ararat region, Armenia) was the capital of the Armenian Kingdom of the Artaxiads, founded in the eighties of the 2nd century BC, but even before this the site was occupied in the Chalcolithic period, (ca. 5200-3500 BC), Early Iron Age (ca. 1200-900 BC) and in the Urartian period (ca. 800-600 BC) as well. All the previous occupation phases showed communities that made extensive use of earthen constructions as determined during past and recent archaeological excavations. This multidisciplinary study seeks to examine mudbrick architecture as a proxy for environmental and social interactions during the 1st millennium BC combining geoarchaeology, archaeobotany and building archaeology. We analyzed changes and continuities in architectural form and practices, alongside reconstruction of technological and social processes, to identify issues of raw material procurement, attestation of re-use, and consistency of building practices. The results of the geoarchaeological analysis of the earthen building materials used in different parts of the ancient city point to a re-use of materials over time.